The Influence Of Corporate Governance Mechanisms, Company Growth, And Audit Quality On Going Concern Audit Opinions And Their Impact On Company Value(Empirical Study On Infrastructure, Transportation, And Logistics Companies In The Indonesia Stock Exchange Period 2019-2021) - Yoshua, Yoshua (Green Publisher Indonesia, 2024)
Topo Da’a is one of sub-ethnic of Kaili tribe in Central Sulawesi, Indonesia. This This study aims to examine the influence of corporate governance mechanisms, company growth, and audit quality on going concern audit opinions and their impact on firm value in infrastructure, transportation, and logistics companies listed on the Indonesia Stock Exchange during the period 2019-2021. The research method used is quantitative descriptive with data analysis through descriptive statistics, classical assumption tests, regression analysis, and model feasibility tests. The analysis results show that the independent variables collectively have a significant effect on going concern audit opinions, but not significant on firm value. The results also indicate that going concern audit opinions do not have a significant direct impact on firm value. Partial test results show that audit quality has a negative and significant effect on going concern audit opinions, while other variables are not significant in influencing the level of going concern audit opinions or firm value. In conclusion, this study provides insights into the factors influencing going concern audit opinions and firm value, providing important implications for practitioners, policymakers, and researchers in the field of accounting and management.